PENGARUH INFLUENCER KUALITAS CITA RASA DAN PELAYANAN PRODUK LOKAL TERHADAP TINGKAT PEMBELIAN PELANGGAN DI COFFE SHOPE SHADO CO RANTAUPRAPAT - Kartika Harahap; Muhammad Irwansyah Hasibuan; Yanto Zelibu (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to determine the influence of local product taste quality and service influencers on customer purchase decisions at Coffee Shope Shadow Co Rantauprapat. The sample size was 171 respondents, namely Coffee Shope Shadow consumers. This study used validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t-tests, F-tests, and coefficients of determination using SPSS 27. The study was conducted to examine how independent variables influence the dependent variable and the percentage level of influence of the research variables by distributing research questionnaires to respondents and conducting tests. The results showed that all independent variables influenced the dependent variable, with all t-values ​​> t-table and significance values ​​<0.05. With a determination level of 0.619, or 61.90%, the effect was positive and significant.